PRODUKSI POLONG DAN BIJI TANAMAN GAMAL (Glirisidia sepium) DARI BERBAGAI PROVENANSI DENGAN PEMUPUKAN NPK - Muh. Restu; Baharuddin Mappangaja (PERENNIAL, 2006)
The productivity of forest natural resources is now decreasing and therefore rehabilitation efforts is urgently needed. Breeding of forest plant is the best solution to increase forest productivity in both quantity and quality. The biological reproduction can be conducted through seed production with fertilization. This research was aimed at determining the effect of fertilizing treatments on pod and seed production of different Glirisidia sepium provenances to find out the best provenance and best fertilizer dosage. Fertilization treatments showed a significant effect on the pod and seed production. On the other hand, the provenance and its interaction with fertilizing did not show any significant effects on the pod and seed production. The best performance was found on the fertilization treatment of 500 g resulting in the average production of 1,288 pods and 27,621 seeds/tree. Keywords: Fertilizing, Seed Production, Provenance, Glirisidia sepium